O ensino da função logarítmica por meio de uma sequência didática ao explorar suas representações com o uso do software GeoGebra - Santos, Adriana Tiago Castro dos (2011)
This study aims at developing, to apply and to analyze a didactic sequence which has involved the logarithm function theme using the software GeoGebra as a pedagogical strategy. For this purpose we have chosen the Registers of Semiotic Representation Theory as theoretical framework, as described by Duval (2009) as well as the Advanced Mathematical Thinking Processes, according to Dreyfus (1991). We have used the project of Didactic Engineering (ARTIGUE, DOUADY, MORENO, 1995) as methodological reference. The activities chosen to compose the sequence were retrieved from Math Teacher´s book of the High School to the first grade third quarter of 2009 (SÃO PAULO, 2009) with some adaptations which we judged necessary. The fellows of this survey were students of a public school in São Paulo State in the town of Itaquaquecetuba who were observed during eight presence meetings. The analyses of the production achieved by the students in connection with the transcriptions of the dialogues recorded in audio during the proposal of the didactic sequence pointed out that there were difficulties in making the conversion from the graphic register in the initial record to the registers: algebraic and in the natural language in the final record. Based on the report of the participants, the use of the software GeoGebra has contributed to the visualization and to the understanding of the graphic performance of the studied functions. The Advanced Mathematical Thinking Processes involved in the strategies of the solutions of the students were: the discovery by using investigation, changing of representation for the same concept, generalization and abstraction. According to Dreyfus (1991) these processes are relevant to the understanding of a mathematical concept. After the analyses of the results we have concluded that the application of the didactical sequences using the software GeoGebra was efficient strategy to achieve our initially proposed objectives